Grape seed extract and L-ascorbic acid exert antineoplastic effects against solid Ehrlich carcinoma in vivo by modulating the tumor microenvironment and Th1/Th2 balance - Morsi, Dalia S.; Hathout, Heba M. R.; AboShabaan, Hind S.; Emam, Mahmoud; El-khadragy, Manal; Abdel Moneim, Ahmed E.; El-Garawani, Islam M.; Abu Quora, Hagar A. (Frontiers in Immunology, 2025)
ObjectiveThe existing study sought to highlight the modulatory effect of co-treatment based on grape seed extract (GSE) and L. ascorbic acid (AA) on tumor microenvironment and immune response in murine solid Ehrlich carcinoma (SEC). MethodsGSE (200 mg / kg; orally) and AA (50 mg/ kg; orally) were given either separately or in a combination for 14 days. GSE active metabolites were identified using GC-MS and LC-MS/MS. Tumor size, Ki-67, Caspase-3, intratumoral infiltrated CD4+, CD8+ and FOXP3+ cells were detected immunohistochemically. Oxidative stress of tumor cells was determined. Serum levels of IL-12, IFN-γ, IL-4 and IL-10 were detected using ELISA. Results and discussionThe results revealed treatment with GSE and/or AA markedly diminished tumor size, intensified intratumoral oxidative stress, downregulated tumor cell proliferation along with upregulated tumor cells’ apoptosis. GSE and AA enhanced tumor immune microenvironment through increasing CD8+ and CD4+ T cells accompanied by decreasing FOXP3+ Treg cells infiltrated in tumors. GSE and/ or AA moved Th1/Th2 balance in favor of Th1 as evidenced by increased serum levels of IFN-γ and IL-12 accompanied with decreased serum levels of IL-4 and IL-10. These findings may be attributed to the presence of different chemical scaffolds of phenolic acids, Flavan-3-ols and its glycosides, glycerolipids and its glycosides, glycosylated seco-iridoids, dihydrochalcone, stilbenoid, flavone, dihydroxyflavone, and methylated flavone, sugars, and fatty acids. In conclusion, results suggested that dual treatment based on GSE & AA are promising anticancer therapeutics, through their potency to control proliferation, induce apoptosis, intratumoral oxidative stress, modulate tumor immune microenvironment and shifting Th1/Th2 response toward Th1